Automation and robotics in the context of Industry 4.0: the shift to collaborative robots. Issue 3 (May 2019) - Galin, Rinat; Meshcheryakov, Roman
Abstract: This paper describes the role and place of collaborative robotics of industrial automation in the context of rapid industrial development. Collaboration of humans and robots in close proximity in a single work space is a stimulating feature of Industry 4.0. Urgent research issues in the field of industrial robotics include problems of developing safer robots in human-machine interaction systems. Due to the close collaboration between humans and robots, many of the problems of industrial robotics are associated not only with technical issues, but also with social aspects. Optimization and automation of production through the introduction of robotic solutions is widely used. In future it will become the basis of all business processes.